Malignant Transformation of Temporal Bone Schneiderian Papilloma Associated with HPV-6. (25th January 2021) - Marzouk, O.; Brasch, F.; Todt, I.; Goon, P. K. C.; Sudhoff, H.
Abstract : Introduction . Temporal bone Schneiderian papillomas (TBSPs) rarely present as a primary tumors arising from the middle ear and mastoid process. The clinical findings and imaging of TBSPs are not specific. Therefore, diagnosis can only reliably be definitively established by histopathology. Objective . To report a novel case of a malignant transformation of TBSP associated with HPV-6 and to present its management. Case Report . A 68-year-old woman presented with conductive hearing loss and recurrent right-sided otorrhoea. Initially, we performed a lateral temporal bone resection and obliteration with abdomen fat. Early histology described TBSP associated with HPV-6. Follow-up detected malignant transformation of the Schneiderian papillomatous variant. Postoperative radiotherapy combined with extended temporal bone resection resulted in a disease-free 17-month period of follow-up. Discussion . TBSPs are not very specific, and the diagnosis can only reliably be established by histopathology. There is a risk of malignant transformation, and due to the absence of reliable prognostic markers, strict postoperative follow-up is mandatory and should consist of regular otoscopy, nasal endoscopy, and imaging. This case also supports the importance of extended temporal bone resections as salvage surgery, combining radical surgery with radiotherapy for improved survival rates.